The Practical Approach to Care Kit (PACK) training programme: scaling up and sustaining support for health workers to improve primary care. (14th November 2018) - Simelane, Makhosazana Lungile; Georgeu-Pepper, Daniella; Ras, Christy-Joy; Anderson, Lauren; Pascoe, Michelle; Faris, Gill; Fairall, Lara; Cornick, Ruth
Abstract : There is an urgent need to depart from in-service training that relies on distance and/or intensive off-site training leading to limited staff coverage at clinical sites. This traditional approach fails to meet the challenge of improving clinical practice, especially in low-income and middle-income countries where resources are limited and disease burden high. South Africa's University of Cape Town Lung Institute Knowledge Translation Unit has developed a facility-based training strategy for implementation of its Practical Approach to Care Kit (PACK) primary care programme. The training has been taken to scale in primary care facilities throughout South Africa and has shown improvements in quality of care indicators and health outcomes along with end-user satisfaction. PACK training uses a unique approach to address the needs of frontline health workers and the health system by embedding a health intervention into everyday clinical practice at facility level. This paper describes the features of the PACK training strategy: PACK training is scaled up using a cascade model of training using educational outreach to deliver PACK to clinical teams in their health facilities in short, regular sessions. Drawing on adult education principles, PACK training empowers clinicians by using experiential and interactive learning methodologies to draw on existing clinical knowledge and experience. Learning is alternated with practice to improve the likelihood of embedding the programme into everyday clinical care delivery.